2022
DOI: 10.3389/fphar.2022.1031969
|View full text |Cite
|
Sign up to set email alerts
|

Prospective population pharmacokinetic study of tacrolimus in adult recipients early after liver transplantation: A comparison of Michaelis-Menten and theory-based pharmacokinetic models

Abstract: Background and Objective: Tacrolimus, a calcineurin inhibitor widely used as a potent immunosuppressant to prevent graft rejection, exhibits nonlinear kinetics in patients with kidney transplantation and nephrotic syndrome. However, whether nonlinear drug metabolism occurs in adult patients undergoing liver transplantation remains unclear, as do the main underlying mechanisms. Therefore, here we aimed to further confirm the characteristics of nonlinearity through a large sample size, and determine the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The nonlinear pharmacokinetic behavior of tacrolimus has been used to explain its pharmacokinetics in patients who underwent kidney and liver transplantation [33][34][35]. The results of these studies demonstrated signi cantly improved testing outcomes, speci cally in the range of tacrolimus levels used in patients who underwent kidney and liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The nonlinear pharmacokinetic behavior of tacrolimus has been used to explain its pharmacokinetics in patients who underwent kidney and liver transplantation [33][34][35]. The results of these studies demonstrated signi cantly improved testing outcomes, speci cally in the range of tacrolimus levels used in patients who underwent kidney and liver transplantation.…”
Section: Discussionmentioning
confidence: 99%